2018
DOI: 10.1016/j.neuroimage.2018.04.059
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of dopaminergic and non-dopaminergic neurons to VTA-stimulation induced neurovascular responses in brain reward circuits

Abstract: Mapping the activity of the human mesolimbic dopamine system by BOLD-fMRI is a tempting approach to non-invasively study the action of the brain reward system during different experimental conditions. However, the contribution of dopamine release to the BOLD signal is disputed. To assign the actual contribution of dopaminergic and non-dopaminergic VTA neurons to the formation of BOLD responses in target regions of the mesolimbic system, we used two optogenetic approaches in rats. We either activated VTA dopami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 54 publications
5
46
0
Order By: Relevance
“…A reward-related area which showed deactivation was the ventral pallidum, with reduced activity in the contralateral hemisphere during electrical stimulation. Similarly to previous studies [22,24], we again found no significant activation at the exact fiber position or in the VTA during optogenetic stimulation. In contrast to previous findings, however, the electricalstimulation-induced neuronal activity was too low to cause significant SPECT activation.…”
Section: Spect Imaging In Th::cre Animalssupporting
confidence: 90%
See 1 more Smart Citation
“…A reward-related area which showed deactivation was the ventral pallidum, with reduced activity in the contralateral hemisphere during electrical stimulation. Similarly to previous studies [22,24], we again found no significant activation at the exact fiber position or in the VTA during optogenetic stimulation. In contrast to previous findings, however, the electricalstimulation-induced neuronal activity was too low to cause significant SPECT activation.…”
Section: Spect Imaging In Th::cre Animalssupporting
confidence: 90%
“…Differences exist in frontal cortex and striatum, depending on the line (DAT::Cre: mPFC and OFC; TH::Cre: striatum and IPN). We speculate that these results are related to stimulation of glutamatergic VTA neurons, a side effect of electrical stimulation but not optogenetic VTA stimulation in the lines used [22,23,47]. It should also be noted that due to the relatively weak impact of dopamine on metabolic signals, one would not expect to find the massive, brain wide activations reported for less-specific stimulation of the dopamine system [24,48].…”
Section: Discussionmentioning
confidence: 86%
“…Finally, the BOLD signal obviously does not directly reflect DA release, and the precise physiological relationship between DA release and BOLD signal is still to be revealed (Knutson & Gibbs, 2007;Brocka et al, 2018). Based on pharmacological MRI studies, it has been suggested that striatal DA release may increase the BOLD signal via a D1-dependent mechanism, according to which D1 receptor activation changes the postsynaptic membrane potential and engages metabolic processes, which in turn lead to increased oxygen utilization followed by an elevated local BOLD response (Knutson & Gibbs, 2007).…”
Section: Neural Da Drug Effectsmentioning
confidence: 99%
“…Based on pharmacological MRI studies, it has been suggested that striatal DA release may increase the BOLD signal via a D1-dependent mechanism, according to which D1 receptor activation changes the postsynaptic membrane potential and engages metabolic processes, which in turn lead to increased oxygen utilization followed by an elevated local BOLD response (Knutson & Gibbs, 2007). However, a recent optogenetic study in rats suggests that canonical BOLD responses in the reward system may mainly represent the activity of non-dopaminergic neurons, such as glutamatergic projecting neurons (Brocka et al, 2018). Thus, it is also conceivable that L-dopa might have enhanced striatal DA release to some degree without triggering a (detectable) BOLD signal change.…”
Section: Neural Da Drug Effectsmentioning
confidence: 99%
See 1 more Smart Citation